Performance Evaluation of XML Enabled Database - Wong, Yen Fatt (2011)
XML Enabled Database (XEnDB) refers to existing relational.object oriented database with features in handling XML. The objective behind this study was to show the effectiveness of a database system with implemented features to handle XML functionalities as opposed on relying on middle-tier.